Reconcilation of German and Chinese managerical, strategic and planning approaches for German companies to develop successful joint ventures in the PRC with local partners. - Welscher, Stephen A. (2008)
The dissertation is an active consultancy project for the ‘DaimlerChrysler Management Consulting GmbH’ based in Stuttgart, Germany. The paper’s focus is to develop a consultancy framework to remedy a growing concern amongst German multi-national corporations, especially within the DaimlerChrysler group, in their joint venture activities within the People’s Republic of China.